Navigating Progression and Promotion in Academic Libraries: An Insight by Early Career Indigenous Librarians - MacLeod, Kaia; Paul, Bethany (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
This paper explores tensions faced by Indigenous librarians in Canadian academic libraries and gives a voice to the newer generation of Indigenous librarians. Indigenous librarians deal with varying expectations while navigating academia, such as serving on Equity, Diversity, and Inclusion (EDI) committees and pursuing promotion in a colonial structure that may not appreciate how their time is spent in non-quantifiable ways like relationship building. This leads to the implementation of various coping strategies such as community-seeking outside of the workplace.